Marketing Strategies of Car Makers in the Pre-Owned Car Market in India - Shafiulla, B (Indian Journal of Marketing, 2012)
In India, the equation between the Pre-owned and new cars is 1:1 - that is for every one new car bought, a used car is sold. It is growing faster, at the rate of growth of 26%, in comparison to the 18% growth of the new car market. There is a bigger pool of Pre-owned cars, with more car models being launched. Customers who buy new cars do not usually own it for long, and tend to sell it off in two to three years. Currently, in India, such a trend has started and would catch the full momentum by 2010-2012. Initially, there was no firm offering professional services in the pre-owned car market, as more than 90% of the market share is dominated by the unorganized pre-owned car dealers, and owner to owner transaction is facilitated by individual brokers. This paper examines the reasons for boom in the pre-owned car business and strategic reasons for entry of car makers into the Pre-owned car business in India. Focus is on marketing strategies of car makers in the Pre-owned car market in India. The primary data for this study has been collected through direct interviews by using unstructured questions. A sample of 45 unorganized private pre-owned car dealers and 15 organized pre-owned car dealers was taken from Ahmedabad, Bangalore, Hyderabad and Kolkata. Car Makers’ pre-owned car outlets like "Maruti True Value" of Maruti Suzuki, "FirstChoice" of Mahindra and Mahindra, "Toyota U Trust" of Toyota Motors, and the "Auto Terrace" of Honda Siel Cars India Ltd. are the focus for this study. Secondary data has been collected from various auto magazines, journals and online information. The strategic reasons for entry of car makers into the pre-owned car market are Exchange Offers, Enhanced Resale Value, Customer Retention, and a Competitive Strategy of car makers.